Synergies of affordances and place-based relationality in Forest School practice: implications for socio-emotional well-being - Sharma-Brymer, Vinathe; Brymer, Eric; Willis, Royce; Leach, Matthew (Frontiers in Psychology, 2024)
Research shows that the human-nature relationship positively impacts human well-being. Forest School (FS) practice offers young children a structured program of nature connection through activities, aiming to enhance their self-esteem and social skills. FS is now adapted in countries such as Australia, Canada and New Zealand where a unique cultural interface occurs between European settlers and Indigenous peoples. Responding to socio-cultural diversities, geographical contexts, and the traditional ecological knowledges, FS needs to go beyond play pedagogy and incorporate theoretical perspectives that promote human-nature relationship in local context-specific environments. We argue that the synergies between Western perspectives on affordances perceived in person-environment relationship and Indigenous place-based relationality perspective provide a more suitable approach for developing reciprocal relationships between FS participants and land/place/nature. We propose that the synergies between affordances perceived in FS and place-based relationality cultivated in participants will enhance social and emotional well-being. We call for specific research investigating such synergies supporting participant well-being. Future research on FS practice should be directed toward initiating and exploring co-designed studies by Indigenous and non-Indigenous researchers incorporating methodologies that study participant experience as well as evaluating the impact of FS programs embedding affordances and place-based relationality perspectives.